Democracies Restricting Democratic Rights: Some Classical Sources and Implications for Ethics of Biometrics - Frank J. Leavitt (The Scientific World Journal)
Ancient Greek and 17th century English philosophy are not usually discussed along with the ethics of biometrics and data sharing. Academic ethics today, however, suffers from a lack of background in classical texts. We may discuss whether biometrics and data sharing are consistent with democracy, but if we do not know what democracy is, then we cannot know what actions are consistent with it. I shall discuss how and why democracies have restricted the rights of their citizens. I will give the most attention to two paradigms that have most influenced modern democratic thinking: 17th century English democracy and ancient Athens. I do not accept the dogma that the Athenians were obviously wrong to try and then to condemn Socrates. His death-loving doctrine could not but have weakened the will of the youth to work and fight for the good of Athens. I will try to understand the Athenians' point of view and their need to defend their security. At the end, I will apply these lessons to biometrics and data sharing for security reasons.